Advances in Understanding and Harnessing the Molecular Regulatory Mechanisms of Vegetable Quality - Gao, Luyao; Hao, Ning; Wu, Tao; Cao, Jiajian (Frontiers in Plant Science, 2022)
The quality of vegetables is facing new demands in terms of diversity and nutritional health. Given the improvements in living standards and the quality of consumed products, consumers are looking for vegetable products that maintain their nutrition, taste, and visual qualities. These requirements are directing scientists to focus on vegetable quality in breeding research. Thus, in recent years, research on vegetable quality has been widely carried out, and many applications have been developed via gene manipulation. In general, vegetable quality traits can be divided into three parts. First, commodity quality, which is most related to the commerciality of plants, refers to the appearance of the product. The second is flavor quality, which usually represents the texture and flavor of vegetables. Third, nutritional quality mainly refers to the contents of nutrients and health ingredients such as soluble solids (sugar), vitamin C, and minerals needed by humans. With biotechnological development, researchers can use gene manipulation technologies, such as molecular markers, transgenes and gene editing to improve the quality of vegetables. This review attempts to summarize recent studies on major vegetable crops species, with Brassicaceae, Solanaceae, and Cucurbitaceae as examples, to analyze the present situation of vegetable quality with the development of modern agriculture.